2019
DOI: 10.4236/wjcd.2019.912078
|View full text |Cite
|
Sign up to set email alerts
|

Study of Etiological Profile, Clinical Profile and Short Term Outcome of Patients Presenting with Pericardial Effusion in a Tertiary Care Center, Nepal

Abstract: Introduction: Pericardial effusion is one of the common cardiac problems in our part of the world and adds burden to the health and economy of the country, as it is associated with high risk of morbidity and mortality. Our objective of the study was to determine the etiological spectrum of pericardial effusion, their clinical presentations and complications and assessing the usefulness of echocardiographic features of effusion in helping to determine the etiology. Methods: A cross-sectional observational prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…This is in harmony with previous reports from developing countries [ 8 , 15 , 21 ]. This contrasts with studies from other developing countries where mycobacterium tuberculosis was the common etiologic agent [ 9 11 , 22 , 23 ]. Whereas Ethiopia is a TB endemic country our findings should be interpreted in light of the short duration of an illness among our study subjects with a median duration of illness of about two weeks.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…This is in harmony with previous reports from developing countries [ 8 , 15 , 21 ]. This contrasts with studies from other developing countries where mycobacterium tuberculosis was the common etiologic agent [ 9 11 , 22 , 23 ]. Whereas Ethiopia is a TB endemic country our findings should be interpreted in light of the short duration of an illness among our study subjects with a median duration of illness of about two weeks.…”
Section: Discussioncontrasting
confidence: 61%
“…This is similar to other studies [ 10 , 21 ]. However, a reverse was documented in another study [ 11 ]. In this study, significant number of deaths happened at home after hospital discharge and majority had pericardiocentesis done earlier, it could be due to recollection and a missed opportunity for life saving pericardiocentesis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Similar to the study, the most common presenting symptom in our study was breathlessness in 85% followed by tachycardia in 56% of the patient. Study done by Khanal, R. et al 9 showed most common clinical feature shortness of breath (95%) followed by tachycardia (63.4%).…”
Section: Discussionmentioning
confidence: 95%